1992
DOI: 10.1128/jvi.66.5.2679-2688.1992
|View full text |Cite
|
Sign up to set email alerts
|

Ovine lentivirus is macrophagetropic and does not replicate productively in T lymphocytes

Abstract: The lentiviruses of sheep, goats, and horses cause chronic multiorgan disease in which macrophages are highly permissive for viral replication. Monocytes, which mature into macrophages, are thought to be latently infected with lentivirus, but the extent to which other leukocytes are infected is unknown. Dendritic cells have not been studied separately from monocytes and T-cell subsets have not been examined in previous attempts to identify infected cells in peripheral blood mononuclear cells (PBMC). We found n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 70 publications
1
39
0
2
Order By: Relevance
“…Both HIV and OPPV are macrophage‐tropic lentiviruses that cause lifelong persistent infection in the host (Gendelman et al. 1986; Gorrell et al. 1992; Thormar 2005; Alkhatib & Berger 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Both HIV and OPPV are macrophage‐tropic lentiviruses that cause lifelong persistent infection in the host (Gendelman et al. 1986; Gorrell et al. 1992; Thormar 2005; Alkhatib & Berger 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is closely related biologically to lentiviruses that infect other species, including those producing immunosuppressive disease [2][3][4][5][6][7]. It differs from most of the lentiviruses in that the MVV is considered to infect solely the cells of the monocyte-macrophage series [8], contrasting with the usual concurrent lymphocyte and monocytemacrophage lentivirus infection. MVV is also unusual in that there is little evidence of clinically significant virally induced immunosuppression, and no recognized patterns of secondary infection [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…This finding would suggest that although lentiviruses both in humans and sheep induce inflam-matory changes by similar mechanisms, they differ in some aspects of their pathogenesis. Further investigations are required to determine if the decrease in CD4' T lymphocytes reflects an infection in some cells of this lymphocytic subset, However, recent work demonstrated that sheep lentivirus is not lymphocytotropic and does not replicate productively in CD4' T lymphocytes obtained from blood and lymph [28]. Therefore, other explanations are needed for the CD4' T cell reduction.…”
Section: Discussionmentioning
confidence: 99%